Comparison of Neutrophil Lymphocyte Ratio and Platelet Lymphocyte Ratio levels in ovarian cyst among epithelial ovarian cancer patients at RSUP H. Adam Malik Medan, Indonesia - Sari Dewi, Mega; Yustin Simanjuntak, Roy; Sari Lintang, Letta; Fahdhy, Muhammad; Edianto, Deri; Sitepu, Makmur (Universitas Airlangga, 2023)
HIGHLIGHTS Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) have potential as independent prognostic markers for ovarian cancer. This research was to evaluate NLR and PLR levels in ovarian cysts with epithelial ovarian cancer patients at RSUP H. Adam Malik Medan, Indonesia. ABSTRACT Objective: To assess Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) as independent prognostic markers in epithelial ovarian cancer patients at RSUP H. Adam Malik Medan, Indonesia, considering the disease's common occurrence and typically late-stage diagnosis with a poor prognosis due to inflammatory processes implicated in malignancy mechanisms. Materials and Methods: A comparative case-control study was conducted at the Department of Obstetrics and Gynecology, RSUP H. Adam Malik Medan, from December 2019 to February 2020. The study included 40 patients each diagnosed with ovarian cysts and epithelial ovarian cancer. Bivariate analysis was conducted using independent T-test for normally distributed data and the Mann-Whitney test for non-normally distributed data. Significance was established at p <0.05. Results: The median NLR in the ovarian cancer group was 2.45 (1.06 to 38.44) and in the ovarian cysts group was 2.34 (1.44 to 3.78). Median PLR levels in ovarian cancer were 12813.94 (3178.08 to 19040.0) and in ovarian cysts were 11138.15 (5026.18 to 22839.51). Statistical analysis revealed no significant difference in NLR and PLR levels between ovarian cancer and ovarian cysts (p >0.05). Conclusion: NLR and PLR levels demonstrated no significant difference between ovarian cancer and ovarian cyst patients at RSUP H. Adam Malik Medan, Indonesia. However, NLR and PLR can still serve as valuable markers for identifying malignant processes in patients suspected of malignancy.